Bibliometric analysis of Oropouche research: impact on the surveillance of emerging arboviruses in Latin America [version 1; referees: 2 approved] - Carlos Culquichicón; Jaime A. Cardona-Ospina; Andrés M. Patiño-Barbosa; Alfonso J. Rodriguez-Morales (F1000Research, 2017)
Given the emergence and reemergence of viral diseases, particularly in Latin America, we would like to provide an analysis of the patterns of research and publication on Oropouche virus (OROV). We also discuss the implications of recent epidemics in certain areas of South America, and how more clinical and epidemiological information regarding OROV is urgently needed.